2018
DOI: 10.1167/tvst.7.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Qualitative Approach Toward Evaluating OCT Imaging for Detecting Glaucomatous Damage

Abstract: PurposeThe purpose of this study was to determine whether a qualitative approach toward evaluating optical coherence tomography (OCT) imaging improves the ability to detect glaucomatous damage compared to a conventional metric of global circumpapillary retinal nerve fiber layer (cpRNFL) thickness.MethodsA total of 394 healthy eyes and 272 glaucoma eyes were evaluated. Glaucoma eyes were categorized as perimetric (156 eyes) based on a history of three or more consecutive abnormal 24-2 visual field tests or susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…9,10,12,13 As previously shown, it provides information concerning the light sensitivity of several macular points with a very good repeatability. 11,16 The present results show no retinal impairment associated to adalimumab therapy.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…9,10,12,13 As previously shown, it provides information concerning the light sensitivity of several macular points with a very good repeatability. 11,16 The present results show no retinal impairment associated to adalimumab therapy.…”
Section: Discussionsupporting
confidence: 55%
“…Previously, an improvement of the macular sensitivity in a second examination in healthy subjects was reported and also in AMD patients. 11,16 On the other hand, Wong et al reported no learning effect on the mean sensitivity in glaucoma patients by using MAIA microperimetry. 21 In our previous study, a learning effect was seen in fixation stability in the better eye of AMD patients, but there was no learning effect in their worse eye by microperimetry 16 or nor in any eye concerning the other parameters, like sensitivity or macular integrity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also evidence that the cpRNFL thickness measured from circle b-scans, on which the ΔG metric is based, is affected by segmentation and alignment errors 14 18 and that reports based on this metric can miss local defects. 19 21 Our purpose here was to provide evidence that links these findings. That is, we tested the hypothesis that local defects, segmentation errors, and alignment are major contributing factors to the relatively poor performance of the commonly used method to detect progression, that is, the ΔG metric.…”
Section: Discussionmentioning
confidence: 87%